Pathogenesis and Diagnostic Challenges of Mucormycosis - Tari Ambai Sari; Robiatul Adawiyah; Retno Wahyuningsih (Eduvest - Journal of Universal Studies, 2024)
Mucormycosis is a fungal infection caused by the order Mucorales from the class Zygomycetes. Among the genera within the order Mucorales, Rhizopus sp. is the genus most frequently causing infections. Mucorales fungi enter the human body in three ways: through inhalation of airborne spores, through broken skin, and through ingestion of contaminated food. Within the human body, the process is angioinvasive, leading to thrombosis and resulting in tissue necrosis. Currently, establishing a diagnosis is crucial for determining the patient’s prognosis, as it can reduce morbidity and mortality. The current diagnostic modes include direct examination, culture, histopathology, and molecular identification. Each of these methods has its advantages and disadvantages. However, for rapid diagnosis, molecular examination, either through PCR or RT PCR, is necessary.